Opportunities and challenges for Vietnam's social order in the digital economy - Chuyen, Truong Hong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
The acceleration of information technology has oriented the development of a digital society where a new social order was formed based on data relationships. The research used a systematic literature review and qualitative research methods to explore the characteristics of new social order in an AI-enabled world. The research aims to identify the formation of new social order and its impacts on the socio-economic development in Vietnam. The results contributed to theories of transcendental phenomenology, social construction, and urbanism. The results identified intertwined opportunities and challenges for Vietnamese digital society, including social identity management, smart urban infrastructure management, and data colonialism. Recommendations suggested a transformative strategy based on a collaboration between government, education, and business to develop human capital concerning digital citizenship, culture reinforcement, and social support.